2015
DOI: 10.1080/17470919.2015.1040893
|View full text |Cite
|
Sign up to set email alerts
|

RNAi knockdown of oxytocin receptor in the nucleus accumbens inhibits social attachment and parental care in monogamous female prairie voles

Abstract: Oxytocin modulates many aspects of social cognition and behaviors, including maternal nurturing, social recognition and bonding. Natural variation in oxytocin receptor (OXTR) density in the nucleus accumbens (NAcc) is associated with variation in alloparental behavior, and artificially enhancing OXTR expression in the NAcc enhances alloparental behavior and pair bonding in socially monogamous prairie voles. Furthermore, infusion of an OXTR antagonist into the nucleus accumbens (NAcc) inhibits alloparental beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 67 publications
4
119
0
Order By: Relevance
“…This work indicates critical roles of multiple neurochemical systems in the regulation of behaviors associated with pair-bonding including oxytocin (Bales et al, 2007b; Keebaugh et al, 2015; Ross et al, 2009; Williams et al, 1994), vasopressin (Lim et al, 2004; Lim and Young, 2004; Pitkow et al, 2001), dopamine (Aragona and Wang, 2009; Hostetler et al, 2011; Resendez et al, 2016), and opioid systems (Burkett et al, 2011; Resendez et al, 2013; Resendez et al, 2016; Resendez et al, 2012). In contrast, no work to our knowledge has examined serotonergic involvement in pair-bonding in the prairie vole, and little work has examined serotonergic influences on social behavior more generally in this species.…”
Section: Introductionmentioning
confidence: 89%
“…This work indicates critical roles of multiple neurochemical systems in the regulation of behaviors associated with pair-bonding including oxytocin (Bales et al, 2007b; Keebaugh et al, 2015; Ross et al, 2009; Williams et al, 1994), vasopressin (Lim et al, 2004; Lim and Young, 2004; Pitkow et al, 2001), dopamine (Aragona and Wang, 2009; Hostetler et al, 2011; Resendez et al, 2016), and opioid systems (Burkett et al, 2011; Resendez et al, 2013; Resendez et al, 2016; Resendez et al, 2012). In contrast, no work to our knowledge has examined serotonergic involvement in pair-bonding in the prairie vole, and little work has examined serotonergic influences on social behavior more generally in this species.…”
Section: Introductionmentioning
confidence: 89%
“…57 Further evidence for the critical role of OXTR in social functioning comes from animal models demonstrating that dense expression of the oxytocin receptor in the nucleus accumbens (NAcc) is associated with social affiliative behaviors, 8 reduces susceptibility to early adverse experiences (for example, neglect) 9 and critically, that allelic variation in the OXTR is associated with variability in receptor expression specifically in brain areas important for social attachment, including the NAcc. 10 Further, disruption of oxytocin receptor signaling in the NAcc inhibits social attachment 11,12 and the formation of positive associations with social rewards. 13 Together, these studies suggest that oxytocin receptor function in the NAcc is required to form associations with social rewards through its effects on neural excitability in reward-related brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research showed that genetic variations in the OT-receptor gene (OXTR) of prairie voles are related to social attachment and partner preference (King et al, 2015), and that knock-down of the OT receptor inhibited social attachment and parental care (Keebaugh et al, 2015). Also in human infants, polymorphisms in the OXTR gene have been associated with variations in attachment security (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%